Seasonal variation in the nature of DOM in a river and drinking water reservoir of a closed catchment. (January 2017) - Awad, John; van Leeuwen, John; Chow, Christopher W.K.; Smernik, Ronald J.; Anderson, Sharolyn J.; Cox, Jim W.
Abstract: Dissolved organic matter (DOM) in surface waters used for drinking purposes can vary markedly in character depending on its source within catchments and the timing and intensity of rainfall events. Here we report the findings of a study on the character and concentration of DOM in waters collected during different seasons from Myponga River and Reservoir, South Australia. The character of DOM was assessed in terms of its treatability by enhanced coagulation and potential for disinfection by-product i.e. trihalomethane (THM) formation. During the wet seasons (winter and spring), water samples from the river had higher DOC concentrations ( X ¯ : 21 mg/L) and DOM of higher average molecular weight (AMW: 1526 Da) than waters collected during the dry seasons (summer and autumn: DOC: 13 mg/L; AMW: 1385 Da). Even though these features led to an increase in the percentage removal of organics by coagulation with alum (64% for wet compared with 53% for dry season samples) and a lower alum dose rate (10 versus 15 mg alum/mg DOC removal), there was a higher THM formation potential (THMFP) from wet season waters (treated waters: 217 μg/L vs 172 μg/L). For reservoir waters, samples collected during the wet seasons had an average DOC concentration ( X ¯ : 15 mg/L), percentage removal of organics by alum (54%), alum dose rates (13 mg/mg DOC) and THMFP (treated waters: 207 μg/L) that were similar to samples collected during the dry seasons (mean DOC: 15 mg/L; removal of organics: 52%; alum dose rate: 13 mg/mg DOC; THMFP: 212 μg/L for treated waters). These results show that DOM present in river waters and treatability by alum are highly impacted by seasonal environmental variations. However these in reservoir waters exhibit less seasonal variability. Storage of large volumes of water in the reservoir enables mixing of influent waters and stabilization of water quality. Graphical abstract: Highlights: Seasonal variation has a significant effect on organics in river waters. River waters in wet seasons have higher THM formation compared with dry seasons. Storage of large volumes of water in the reservoir results in consistency in DOM. Treatability of DOM in reservoir is less seasonally variable compared with river. Abstract : Concentrations of DOM, relative abundances of coagulable organics and THMFP of treated river waters were impacted by catchment runoff and flow patterns while these for reservoir waters were less seasonally variable.